Analisis Penerapan Akuntansi Manajemen Lingkungan dalam Meningkatkan Inovasi Produk - Hanifah Mulyani; Rini Lestari; Nurleli . (Jurnal Akuntansi Bisnis dan Ekonomi, 2019)
The existence of the facts of environmental pollution problems undertaken by manufacturing companies as a result of the company's production process are mostly found in Indonesia. This causes a business environment must be able to maintain its business processes so that the company must implement appropriate strategies for the achievement of the company's going concern and sustainable development. Thus the demand for environmentally friendly products should be a concern in the continuous development of the industry. This study was conducted with the aim to analyze the application of environmental management accounting in improving the product innovation, in Industry Pabrik Tahu Jembar Manah. The research used an analytical descriptive method. The data source used is the primary data source. The data collection techniques used are interviews and questionnaires. The results show that the company has applied neutral environmental management accounting and good product innovation. This indicates that the Pabrik Tahu Jembar Manah has implemented an environmental management accounting that produces information for owners and managers in which environmental management accounting provides control over factory activities, but does not report environmental costs and does not report revenue on waste recycling management. In addition, the application of good product innovation will improve the ability of Pabrik Tahu Jembar Manah to create a quality product, so it can be said that environmental management accounting is a control tool to improve product innovation.